The notion of subject in the A.Badiou’s Event of Truth conception - Kusherets, Tamara (Actual Problems of Mind, 2017)
The paper explains a content of the notion of subject elucidated by a modern French researcher Alen Badiou in his critical examination of the categories «being» and «truth». The subject is considered as such that distinguishes the traces of truth in some event, names it, and actively champions its accomplishment.